MODIFIKASI STRUKTUR INTERFACE TIPE DECK-ON-PILE UNTUK MENDUKUNG FUNGSI GANDA: JEMBATAN DAN CONTAINER YARD STUDI KASUS TERMINAL KALIBARU PELABUHAN TANJUNG PRIOK - Nur Laili Safitri; Muhammad Agung Prasetyo; Sulastri Iskandar; Wahyu Inggar Fipiana (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
This study discusses the modification of the interface pier structure at the Kalibaru Container Terminal, Tanjung Priok Port or NPCT (New Priok Container Terminal), where the existing condition functions as a connecting bridge between the existing container yard (CY-57) and the reclamation area, now it has an additional function as a container storage reserve area. The purpose of this study is to determine the reliability of the structural design against the loads acting on the structure and to determine the forces that occur and the effect of the reduction in foundation strength due to modifying the interface deck-on-pile structure. Structural analysis uses SAP2000 software while pile foundation analysis is analyzed with Ensoft LPILE, and technical drawing with AutoCAD. The results of the study show that the Interface structure is larger than the original design due to the addition of container stack loads and Loading Unloading activities and the dimensions of the structural elements have changed from the initial design both in the foundation, pilecap, beam and plate. This study shows that the modification of the deck-on-pile interface can support dual functions as a connecting bridge and a container storage reserve area effectively and safely.